PENGEMBANGAN MODEL PASSING BAWAH BOLAVOLI MELALUI PENDEKATAN PERMAINAN TRADISIONAL GATRIK DI SMPN 3 PARONGPONG KABUPATEN BANDUNG BARAT - Rohendi, Aep (Jurnal Olahraga, 2015)
The his research aims to develop a passing model under Volleyball through the basic motion approach of traditional gatric games. This research was conducted at SMPN III Parongpong, West Bandung Regency. The research and development of this learning model uses Research & Development (R & D) research development methods. This research was conducted in 8 steps, the first time it was determined was an idea that would be developed, the second product design, the third evaluation to improve and perfect the manuscript, the four revisions of product I, carried out by the relevant experts, the five prototype products, carried out with product image taking, sixth prototype testing, testing of field subjects both in phase I and phase II trials, the seven second product revisions, the revisions carried out by experts, the eight reproductions, the product refinement to get to the final product. From these stages, the results of the study were obtained with the first stage of evaluation analysis with ten products produced a total number of respondents obtained the amount of data = 123 Thus the effectiveness of the new teaching method as a whole = 123: 144 = 0.85 or 85% of criteria which is expected and based on the second phase of evaluation analysis using the final product amounted to the total score of the respondents produced. obtained amount of data = 246. Thus the effectiveness of the overall teaching method = 246: 288 = 0.85 or 85% of the expected criteria so that it meets valid criteria. Based on the results of these studies it can be concluded that: (1) With the learning model of passing under volleyball through the traditional gatric game approach in junior high school, it is very much needed by physical education teachers and able to improve learning effectively and efficiently. (2) with the learning model that researchers have developed, students are more motivated and active in following the learning process